The Effect of Environmental, Social, and Governance (ESG) Disclosure on Financial Performance of Companies Listed on the IDX ESG Leaders Index (IDXESGL) from 2021 to 2023 - Lita, Eriska Mei; Faisol, Ahmad (Economics and Digital Business Review, 2025)
This study aims to examine the effect of Environmental, Social, and Governance (ESG) disclosure on corporate financial performance, measured using Return on Assets (ROA), in companies listed in the IDX ESG Leaders Index for the 2021–2023 period. The independent variables in this study are the disclosure of Environmental, Social, and Governance aspects, while the control variables include firm size and leverage. Secondary data were obtained from annual reports and sustainability reports, resulting in 78 observations through purposive sampling. The results indicate that Environmental and Social disclosures have a positive and significant effect on financial performance, whereas Governance disclosure does not show a significant impact. Simultaneously, ESG variables significantly contribute to explaining ROA variability. This study implies that implementing sustainability principles through ESG disclosure can enhance financial performance, strengthen competitiveness, and improve legitimacy in the eyes of stakeholders. This research is expected to serve as a reference for companies, investors, and regulators in supporting sustainability implementation in the Indonesian business sector.